Exercise training for people following lung resection for non-small cell lung cancer - A Cochrane systematic review - Cavalheri, Vinicius; Tahirah, F.; Nonoyama, M.; Jenkins, Susan; Hill, Kylie (W B Saunders co Ltd, 2014)
Objectives: To determine the effects of exercise training on exercise capacity, health-related quality of life (HRQoL), lung function (forced expiratory volume in one second (FEV1)) and quadriceps force in people who have had a recent lung resection for non-small cell lung cancer (NSCLC).Data sources: We searched the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, SciELO and PEDro up to February 2013. Review methods: We included randomised controlled trials (RCTs) in which study participants with NSCLC, who had recently undergone lung resection, were allocated to receive either exercise training or no exercise training. Two review authors screened and identified the studies for inclusion. Results: We identified three RCTs involving 178 participants. On completion of the intervention period, exercise capacity, as measured by the six-minute walk distance, was statistically greater in the intervention group compared to the control group (mean difference (MD) 50.4 m; 95% confidence interval (CI) 15.4–85.2 m). No between-group differences were observed in HRQoL (standardised mean difference (SMD) 0.17; 95% CI -0.16–0.49) or FEV1 (MD -0.13 L; 95% CI -0.36–0.11 L). Differences in quadriceps force were not demonstrated on completion of the intervention period. Conclusions: Evidence from our review suggests that exercise training may potentially increase the exercise capacity of people following lung resection for NSCLC. The findings of this review should be interpreted with caution due to disparities between the studies, methodological limitations, some significant risks of bias and small sample sizes.